2018
DOI: 10.1287/opre.2017.1653
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Priority Online Scheduling with Cancellations

Abstract: We study a fundamental model of resource allocation in which a finite amount of service capacity must be allocated to a stream of jobs of different priorities arriving randomly over time. Jobs incur costs and may also cancel while waiting for service. To increase the rate of service, overtime capacity can be used at a cost. This model has application in healthcare scheduling, server applications, make-to-order manufacturing systems, general service systems, and green computing. We present an online algorithm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…More comprehensive reviews can be found in Cayirli and Veral (2003), Gupta andDenton (2008), andAhmadi-Javid et al (2017). The appointment scheduling literature is often classified as either intraday or multiday scheduling (Wang & Truong, 2017). Intraday scheduling is focused on determining optimal sequences and/or appointment times for patients where the number of patients scheduled during a given day is generally fixed.…”
Section: Appointment Schedulingmentioning
confidence: 99%
“…More comprehensive reviews can be found in Cayirli and Veral (2003), Gupta andDenton (2008), andAhmadi-Javid et al (2017). The appointment scheduling literature is often classified as either intraday or multiday scheduling (Wang & Truong, 2017). Intraday scheduling is focused on determining optimal sequences and/or appointment times for patients where the number of patients scheduled during a given day is generally fixed.…”
Section: Appointment Schedulingmentioning
confidence: 99%
“…In a setting where arriving customers can consume multiple units of a particular resource, and where the goal is simply to maximize the number of units consumed, Stein et al (2020) develop a 0.321-approximation scheme. Wang et al (2018) consider an online matching setting that is almost identical to ours, and provide an approach that is…”
Section: Online Matchingmentioning
confidence: 99%
“…To evaluate the performance of an online algorithm L , we adapt CR as our performance criterion. CR is a widely used performance metric for online algorithms with various applications, including the scheduling problems (Stein et al., 2020; Wang & Truong, 2018), order fulfillment problems (Jasin & Sinha, 2015; Zhao et al., 2020), and revenue management problems (Ma et al., 2021a; Ma et al., 2021b).…”
Section: Modelmentioning
confidence: 99%